PENGARUH PENERAPAN BAURAN PEMASARAN TERHADAP TINGKAT KEPUASAN KONSUMEN DALAM JASA PELAYANAN DI RSU SURYA HUSADHA - Putri Anggreni (Forum Manajemen STIMI Handayani Denpasar, 2012)
Hospital represent one of example institute the service in healtharea. At the height of the requirement and society awareness in the ﬁ eld of healthaccompanied with the change of patterned thinking of society which of opinion thehealth is very important investment in their live, have pushed a lot of party to exploitto existing market opportunity by development building various to like hospital. Inthe development it is effort the hospital do not get out of the compulsion to apply themanagement process in it is effort consumer satisfaction presented is very importantnecessary for the peripatetic company in service area like to hospital. And one ofstrategy which can by run the hospital to take care of the consumer satisfaction with the maximization to applying of the marketing mix in the company activities as far becoming formula oppositely, also how inﬂ uence to applying of the marketing mix toconsumer satisfaction in using the service in Surya Husadha Hospital? How strengthof relation to applying of the marketing mix to consumer satisfaction in using theservice in Surya Husadha Hospital? At the research, analysis the information used istechnique is Multiple Regression Analysis with this analysis in Multiple RegressionAnalysis to know there is do not in inﬂ uence of between two variable is the freevariable and the trusted variable. Correlation analysis and determination analysisdo know how inﬂ uence of the marketing mix practices to consumer satisfactionF-Test and t-Test. Pursuant to obtained by Multiple Regression Analysis to resultof is exixtence of real inﬂ uence and is positive than marketing mix to consumersatisfaction at Surya Husadha Hospital is a 4.427. From obtained the CorrelationAnalysis the result of is existence which positive and strong relation of the marketingmix to consumer satisfaction at Surya Husadha Hospital scale 0.792. From thedetermination analysis obtained by result is 62.7% the most percentage of consumersatisfaction inﬂ uence to applying of the marketing mix while some minimizinginﬂ uence by other, dissimilar factor is which not checked. From analysis F-Test andt-Test either through entirety and also each variable marketing mix have to effecton consumer satisfaction and his meaning is hypothesis (Ha) accepted. Conclusionwhich can be pulled from research is between applying to of marketing mix toconsumer satisfaction of at Surya Husadha Hospital own to inﬂ uence and relationwhich are positive and strong go together that is Surya Husadha Hospital alwaysimprove the marketing mix applying to be consumer satisfaction to be weaked